2016
DOI: 10.1016/j.psychres.2016.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Expression of positive emotions differs in illness and recovery in anorexia nervosa

Abstract: Highlights The facial expression of women recovered from anorexia nervosa (REC) was studied. REC smiled more than acutely ill participants in response to a positive film. The facial expression of REC was similar to the healthy controls. Facial expressivity in REC was not related to depression or anxiety. AbstractPeople with Anorexia Nervosa (AN) display reduced facial expression of emotions.This study investigated the expression of positive affect in response to a film, examining Duchenne and non-Duchenne … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…Additionally, the present results also replicate previous findings that reduced facial expressivity may be part of acute illness and possibly exaggerated by starvation [17, 18]. One possible interpretation of these findings is that reduced expression in the acute stage of illness is part of maladaptive emotion regulation based on avoidance and suppression.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Additionally, the present results also replicate previous findings that reduced facial expressivity may be part of acute illness and possibly exaggerated by starvation [17, 18]. One possible interpretation of these findings is that reduced expression in the acute stage of illness is part of maladaptive emotion regulation based on avoidance and suppression.…”
Section: Discussionsupporting
confidence: 90%
“…These studies have reported no significant differences between recovered and HC participants in expression of positive or negative affect in response to emotionally provoking film clips [17, 18]. However, further research is required to gain a clear understanding of emotion expression in different forms of ED and different stages of recovery.…”
Section: Introductionmentioning
confidence: 99%
“…A key challenge in examining the relationship between AN and ASD is the fact that the starvation, depression and anxiety symptoms present in AN can also contribute to these cognitive and social problems, rather than indicating the presence of an underlying neurodevelopmental disorder [ 30 32 ]. However, these difficulties have been found to precede the onset of AN in childhood, and to persist to a less severe extent following weight gain and recovery [ 13 , 18 , 27 , 31 , 33 35 ]. This suggests that these problems may for some individuals represent underlying traits that preceded the onset of the disorder, rather than symptoms resulting from starvation: a recent case series study identified a number of individuals with AN and ASD traits with longstanding neurodevelopmental difficulties, confirming a genuine overlap in some individuals between the two disorders [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Individuals subjected to starvation, even without the psychological symptoms of an ED, display certain characteristics of ASD, including reduced cognitive flexibility and social motivation (Keys et al 1950 ). Interestingly, individuals recovered from AN do not show some of the symptoms of ASD, such as difficulties with emotion expression, to the same extent as those who are acutely unwell (Dapelo et al 2016 ). Younger people with AN appear to have less difficulty with central-coherence and set-shifting (Lang et al 2015 ; Westwood et al 2016 ) than adults, suggesting that these inefficiencies are exacerbated by the disorder.…”
Section: Introductionmentioning
confidence: 99%